2021
DOI: 10.1038/s41598-021-04187-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bone transport for ankle arthrodesis as a limb salvage procedure for the treatment of septic pilon fracture nonunion

Abstract: Septic nonunion of the pilon region with ankle joint infection is challenging for orthopedic surgeons to treat and is associated with a high risk of limb loss. Therefore, the aim of this study was to evaluate the effectiveness of bone transport for ankle arthrodesis in salvaging the limp after septic ankle destruction of the pilon region. We conducted a single-center, retrospective study including 21 patients treated for septic pilon nonunion with accompanying septic ankle destruction via Ilizarov bone transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Other studies have demonstrated union rates of 80% to 100%, with larger series such as Fragomen et al 17 and Zarutsky et al 61 achieving a union rate of 84% and 80%, respectively. 4,19,21,22,28,29,38,41,48 We identified 3 risk factors for nonunion-poor soft tissue conditions, addition of subtalar fusion, and increased age, consistent with the current literature in ankle fusion. 6,44,45 Tibiotalocalcaneal fusion has been associated with lower union rates compared with isolated tibiotalar fusion.…”
Section: Radiologic Outcomessupporting
confidence: 82%
See 3 more Smart Citations
“…Other studies have demonstrated union rates of 80% to 100%, with larger series such as Fragomen et al 17 and Zarutsky et al 61 achieving a union rate of 84% and 80%, respectively. 4,19,21,22,28,29,38,41,48 We identified 3 risk factors for nonunion-poor soft tissue conditions, addition of subtalar fusion, and increased age, consistent with the current literature in ankle fusion. 6,44,45 Tibiotalocalcaneal fusion has been associated with lower union rates compared with isolated tibiotalar fusion.…”
Section: Radiologic Outcomessupporting
confidence: 82%
“…This is consistent with results from multiple other studies reporting high complication and reoperation rates ranging from 30% to 60% in various groups of these complex procedures. 17,22,48,53,61 However, in many of the previous studies, the populations studied were not similar, the complications were not classified in a consistent manner, and outcome reporting was also variable; hence, comparisons are not easily made. Even the largest series to date, by Fragomen et al, classified complications according to a system based on general surgery complications, which may not be entirely appropriate.…”
Section: Adverse Events and Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The alternative to lower leg amputation in these cases can be the adaptation of a custom-made orthosis, provided there is no fulminant infection. The attempt to mobilize in an adapted orthosis in cases of partial union or nonunion after Ilizarov arthrodesis without any further internal osteosynthesis has only been described in very few cases, and so far, we are concerned that there are no studies on the further courses of these patients [ 1 , 2 , 4 , 9 , 10 , 13 , 19 ]. The aim of this study was therefore to determine clinical and radiological results in a difficult patient population with orthosis after fixator removal and existing nonunion or partial union.…”
Section: Introductionmentioning
confidence: 99%